2003
DOI: 10.1038/sj.ijir.3901017
|View full text |Cite
|
Sign up to set email alerts
|

Medical therapy for benign prostatic hyperplasia: sexual dysfunction and impact on quality of life

Abstract: Therapies for benign prostatic hyperplasia (BPH) may either improve or exacerbate sexual function with an ensuing impact on quality of life. Here we review a total of 73 papers on medical therapies for BPH with a focus on the effects of different pharmacological agents on sexual function. For example, certain a 1 -adrenergic receptor blockers may improve erectile function; however, ejaculatory dysfunction with one of these agents, tamsulosin, occurs at a rate of 4-18%, rising to 30% with long-term use. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 63 publications
1
52
0
1
Order By: Relevance
“…The main treatment options -besides prostatic surgery -are a-blockers and 5-a reductase inhibitors. 76,77 PDE activity in human prostate tissues was first reported in 1970. 78 Later studies demonstrated that various PDE isoenzymes, including PDE5, are expressed in the prostate.…”
Section: Benign Prostate Syndrome and Lower Urinary Tract Symptoms (Bmentioning
confidence: 99%
“…The main treatment options -besides prostatic surgery -are a-blockers and 5-a reductase inhibitors. 76,77 PDE activity in human prostate tissues was first reported in 1970. 78 Later studies demonstrated that various PDE isoenzymes, including PDE5, are expressed in the prostate.…”
Section: Benign Prostate Syndrome and Lower Urinary Tract Symptoms (Bmentioning
confidence: 99%
“…4,[6][7][8][9] The current analysis from the PCAW program provides one of the largest known studies, which adjusted for the apparent effect of other known risk factors on sexual health including age, comorbidities, smoking and testosterone level. Further to our knowledge, it is the first analysis to address the effect of race on the overall sexual health in a large cohort of men in the USA.…”
Section: Correlation Between Luts and Edmentioning
confidence: 99%
“…Unfortunately, some pharmacological treatments for LUTS/BPH (i.e., a 1 -adrenergic receptor antagonists (a-blockers) and 5a-reductase inhibitors (5ARIs)) are associated with sexual side effects (i.e., ED, EjD and hypoactive sexual desire [HSD]). 18,19 For example, in two US clinical trials in men with LUTS/BPH, treatment with tamsulosin resulted in a higher incidence of EjD (8.4% for tamsulosin 0.4 mg; 18.1% for tamsulosin 0.8 mg) than placebo (0.2%). 20 Furthermore, treatment with a 5ARI, finasteride or dutasteride, is associated with higher incidences of ED, EjD and HSD in men with LUTS/BPH than placebo.…”
Section: Introductionmentioning
confidence: 99%